Pengaruh Model Pembelajaran Kooperatif Tipe Scramble Terhadap Pemahaman Konsep Matematis Siswa SMP - Ria Deswita; M Badrul Aini; Nur Rusliah (Departement of Mathematics Education, 2024)
This research is motivated by the importance of the ability to understand mathematical concepts. This is because mathematical concepts are related to one another so that learning them must be continuous and continuous. But in reality there are still many students who cannot understand the learning concept as a whole. One of the efforts and solutions to overcome this is that there must be an update in the learning model, the Learning Model which is expected to improve students' understanding of mathematical concepts is the scramble type cooperative learning model. The purpose of this study was to determine whether there is an effect of scramble type cooperative learning model on students' understanding of mathematical concepts. This type of research is a experimental research. The population in this study were all seventh grade students at one of the junior high schools in Kerinci. The sample consisted of two classes selected by probability sampling. The instrument used was a test of mathematical concept understanding ability. Data analysis using Independent t-test. Based on data analysis, it was found that there was an effect of scramble type cooperative learning model on students' mathematical concept understanding ability with the average value of the experimental class of 88.03 and the control class of 78.10.